Communication Technology Implementation Through Voice Over Internet Protocol at Nusa Putra University - Wira Harsa Abiyasa Rifki Ghani Harsa; Zaenal Alamsyah (Society : Jurnal Pengabdian Masyarakat, 2026)
Efficient internal communication is essential for educational institutions to support daily operations. This study aims to implement an IP Phone system using VoIP technology as a more flexible and cost-effective alternative to conventional phones. The system was chosen for its ability to utilize existing networks without complex installation. Implementation at Universitas Nusa Putra showed stable, seamless communication across departments and wider coverage. The results indicate that VoIP-based IP Phone systems can serve as a modern, efficient communication solution in campus environments.